2017
DOI: 10.3389/fimmu.2017.00895
|View full text |Cite
|
Sign up to set email alerts
|

Total and High Molecular Weight Adiponectin Expression Is Decreased in Patients with Common Variable Immunodeficiency: Correlation with Ig Replacement Therapy

Abstract: Adiponectin (Acrp30) is an adipokine widely studied for its beneficial metabolic properties. It circulates as low molecular weight (LMW), medium molecular weight (MMW), and high molecular weight (HMW) oligomers. The latter exerts the most potent biological effects. Acrp30 attracted renewed interest with the finding that it was associated with the development and progression of immune disorders. The mechanisms underlying this association and the role of Acrp30 in the pathophysiology of immune-mediated condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…In vivo studies on APN KO mice confirmed that Adiponectin has immunosuppressive effects since these animals present an increase of anti-inflammatory cells and mediators as well as an alteration of M1 (increased TNF-α, and IL-6), and M2 markers, (decreased IL-10) (Ohashi et al, 2010). Finally, human studies have demonstrated a strong modulation of Adiponectin serum concentrations and its receptors in course of immune disorders, powerfully suggesting that Adiponectin has an active role in regulating immune responses (Çoban et al, 2017;Dini et al, 2017;Pecoraro et al, 2017;Lee and Bae, 2018;Polito et al, 2019). Furthermore, it is able to acts also in oxidative stress, indeed Adiponectin in a cancer cells model induces apoptosis and reduce proliferation by oxidative stress in a time-and dose-dependent manner (Van Brocklyn and Williams, 2012).…”
Section: Adiponectin Functionsmentioning
confidence: 74%
“…In vivo studies on APN KO mice confirmed that Adiponectin has immunosuppressive effects since these animals present an increase of anti-inflammatory cells and mediators as well as an alteration of M1 (increased TNF-α, and IL-6), and M2 markers, (decreased IL-10) (Ohashi et al, 2010). Finally, human studies have demonstrated a strong modulation of Adiponectin serum concentrations and its receptors in course of immune disorders, powerfully suggesting that Adiponectin has an active role in regulating immune responses (Çoban et al, 2017;Dini et al, 2017;Pecoraro et al, 2017;Lee and Bae, 2018;Polito et al, 2019). Furthermore, it is able to acts also in oxidative stress, indeed Adiponectin in a cancer cells model induces apoptosis and reduce proliferation by oxidative stress in a time-and dose-dependent manner (Van Brocklyn and Williams, 2012).…”
Section: Adiponectin Functionsmentioning
confidence: 74%
“…In obesity, the excessive expansion of AT mass induces the recruitment of numerous immune cells leading to an imbalance in adipokine production. AT exerts its metabolic function through the production of adipokines, among these is Adiponectin [ 11 , 12 , 13 ]. Literature data demonstrated that obesity strongly correlates to immune and autoimmune disease development [ 11 ].…”
Section: Adipose Tissue: General Characteristicsmentioning
confidence: 99%
“…In addition, in vitro study on chondrocytes suggested that adiponectin promotes rheumatoid arthritis ( Lee et al, 2008 ). On the contrary, Pecoraro et al (2017) reported that adiponectin serum levels in patients affected by common variable immunodeficiency are much lower when compared to controls subjects. Although the fact that adiponectin influences the immune system is well accepted, the underlying molecular mechanisms by which it acts are not yet clear.…”
Section: Adiponectin In Immunitymentioning
confidence: 92%